1976
DOI: 10.1007/bf01972209
|View full text |Cite
|
Sign up to set email alerts
|

Ambivalent role of copper in inflammatory disorders

Abstract: Soluble copper (Cu) preparations are both acute/chronic irritants and effective anti-inflammatory agents in rats. Copper is a prevalent component in several folk remedies for arthritis. Patients with rheumatoid arthritis and ankylosing spondylitis are reported to have higher-than-normal levels of serum copper, mainly associated with albumin. The anti-arthritis drug, D-penicillamine (Pn), efficiently strips Cu from some of its (pharmacologically inert) storage forms, e.g. Cu-albumin, Cu-polynucleotides yielding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1978
1978
1997
1997

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…However, it must also be remembered that from the sixth gold injection onwards the uptake of Cu into the various cytosolic proteins decreased with the decrease in the liver Cu levels. It has been observed that penicillamine, which has similar pharmacologic activity to those of gold sodium thiomalate, can only generate anti-inflammatory activity if there is an endogenous pool of non-caeruloplasmin Cu in vivo [42]. WHITEHOUSE [421 suggested that the poor response of some patients with rheumatoid disease to penicillamine therapy might be due to this lack of non-caeruloplasmin Cu; and in those patients who, after successfully responding to the drug initially for a period of time, no longer benefit from further treatment, might similarly be due to lack of the non-caeruloplasmin Cu.…”
Section: Discussionmentioning
confidence: 99%
“…However, it must also be remembered that from the sixth gold injection onwards the uptake of Cu into the various cytosolic proteins decreased with the decrease in the liver Cu levels. It has been observed that penicillamine, which has similar pharmacologic activity to those of gold sodium thiomalate, can only generate anti-inflammatory activity if there is an endogenous pool of non-caeruloplasmin Cu in vivo [42]. WHITEHOUSE [421 suggested that the poor response of some patients with rheumatoid disease to penicillamine therapy might be due to this lack of non-caeruloplasmin Cu; and in those patients who, after successfully responding to the drug initially for a period of time, no longer benefit from further treatment, might similarly be due to lack of the non-caeruloplasmin Cu.…”
Section: Discussionmentioning
confidence: 99%
“…This has been well established for penicillamine, which can strip albumin-bound Cu(II) [24] and form the very soluble mixed valency (anti-inflammatory) polymer with the composition, [Cu(I)sCu(II)6-pen12C1] 5- [25]. Inspection of the redox potential of Au(I), Au(III), Cu(I) and Cu(II) shows that it is thermodynamically feasible for aurothio anti-arthritic drugs to function as Cu(II)-reductants.…”
Section: Discussionmentioning
confidence: 93%
“…plasma, copper may be redistributed amongst various bioligands and exogenous drugs. Thus Dpenicillamine effectively unbinds Cu(II) from its albumin carrier by displacing the equilibrium in favour of unbound Cu(II), that is removed by rapid reduction to Cu(I) and subsequent complexation with penicillamine [24].…”
Section: Au(iii)mentioning
confidence: 98%
“…The authors of the Multicenter Trial Group [2] who evaluated the use of D-penicillamine in the treatment of rheumatoid arthritis have pointed out that those few drugs which seem to suppress the disease have limitations, so that any new preparation which promises to induce a remission with less hazard is worth close study. Since copper complexes of penicillamine have been found to be much more effective as anti-inflammatory agents than the parent drug [5,6,[13][14][15][16] and they also have antiulcer activity, they should be considered as a new preparation with less hazard for the treatment of rheumatoid arthritis. In this regard, they are worthy of close study in an attempt to facilitate remission of both the articular and extra-articular gastric [4,5] components of arthritic diseases.…”
Section: Discussionmentioning
confidence: 99%